Italian Cardiological Guidelines (COCIS) for Competitive Sport Eligibility in athletes with heart disease: update 2020. Issue 12 (December 2021) - Delise, Pietro; Mos, Lucio; Sciarra, Luigi; Basso, Cristina; Biffi, Alessandro; Cecchi, Franco; Colivicchi, Furio; Corrado, Domenico; D'Andrea, Antonello; Di Cesare, Ernesto; Di Lenarda, Andrea; Gervasi, Salvatore; et al.
Abstract : N/A: Since 1989, SIC Sport and a FMSI, in partnership with leading Italian Cardiological Scientific Associations (ANCE, ANMCO and SIC) have produced Cardiological Guidelines for Completive Sports Eligibility for athletes with heart disease (COCIS – 1989, 1995, 2003, 2009 and 2017). The English version of the Italian Cardiological Guidelines for Competitive Sports Eligibility for athletes with heart disease was published in 2013 in this Journal. This publication is an update with respect to the document previously published in English in 2013. It includes the principal innovations that have emerged over recent years, and is divided into five main chapters: arrhythmias, ion channel disorders, congenital heart diseases, acquired valve diseases, cardiomyopathies, myocarditis and pericarditis and ischemic heart disease. Wherever no new data have been introduced with respect to the 2013 publication, please refer to the previous version. This document is intended to complement recent European and American guidelines but an important difference should be noted. The European and American guidelines indicate good practice for people engaging in physical activity at various levels, not only at the competitive level. In contrast, the COCIS guidelines refer specifically to competitive athletes in various sports including those with high cardiovascular stress. This explains why Italian guidelines are more restrictive than European and USA ones. COCIS guidelines address 'sports doctors' who, in Italy, must certify fitness to participate in competitive sports. In Italy, this certificate is essential for participating in any competition.